Nutritional characteristics of camelina meal for 3-week-old broiler chickens1. (20th February 2015) - Pekel, A. Y.; Kim, J. I.; Chapple, C.; Adeola, O.
Abstract : Limited information on nutritional characteristics on camelina meal for broiler chickens limits its use in diets of broiler chickens. The objectives of this study were to determine the ileal digestible energy (IDE), ME, and MEn contents of 2 different camelina meal (CM1 and CM2) samples for 3-wk-old broiler chickens using the regression method and to determine glucosinolate compounds in the camelina meal samples. The CM1 and CM2 were incorporated into a corn-soybean meal-based reference diet at 3 levels (0, 100, or 200 g/kg) by replacing the energy-yielding ingredients. These 5 diets (reference diet, and 100 and 200 g/kg camelina meal from each of CM1 and CM2) were fed to 320 male Ross 708 broilers from d 21 to 28 post hatching with 8 birds per cage and 8 replicates per treatment in a randomized complete block design. Excreta were collected twice daily from d 25 to 28, and jejunal digesta and ileal digesta from the Meckel's diverticulum to approximately 2 cm proximal to the ileocecal junction were collected on d 28. The total glucosinolate content for CM1 and CM2 were 24.2 and 22.7 nmol/mg, respectively. Jejunal digesta viscosity was linearly increased ( P < 0.001) from 2.2 to 4.1 cP with increasing dietary camelina meal levels. There were linear effects ( P < 0.001) of CM1 and CM2 substitution on final weight, weight gain, feed intake, and G:F. The inclusion of CM1 and CM2 linearly decreased ( P < 0.001) ileal digestibility of DM, energy, and IDE. The supplementation of CM1 and CM2 linearly decreased ( P < 0.001) the retention of DM, nitrogen, and energy; ME, and MEn . By regressing the CM1 and CM2-associated IDE intake in kilocalories against kilograms of CM1 and CM2 intake, the IDE regression equation was Y = −10 + 1, 429 × CM1 + 2, 125 × CM2, r 2 = 0.55, which indicates that IDE values were 1, 429 kcal/kg of DM for CM1 and 2, 125 kcal/kg of DM for CM2. The ME regression was Y = 5 + 882 × CM1 + 925 × CM2, r 2 = 0.54, which implies ME values of 882 kcal/kg of DM for CM1 and 925 kcal/kg of DM for CM2. MEn regression was Y = 2 + 795 × CM1 + 844 × CM2, r 2 = 0.52, which implies MEn values of 795 kcal/kg of DM for CM1 and 844 kcal/kg of DM for CM2. Based on these results, utilization of energy and nitrogen in camelina meal by broiler chickens is low and the high viscosity observed in jejunal digesta as well as the total glucosinolate in camelina meal may have contributed to the poor energy and nitrogen utilization.